Analisis Struktur Kalimat Tunggal dalam Teks Anekdot Di Situs CNN Indonesia. Com - Al Hassanah, Della; Rahmi, Iklima Hilda; Rosialasa, Nabila Ajeng Fransisca; Nur Amin, Muhamad Rizki; Lisnawati, Iis (Universitas Negeri Padang, 2025)
This study aims to examine the use of simple sentences in anecdotal texts published on CNNIndonesia.com. Employing a descriptive qualitative approach, the research analyzes five anecdotal texts titled